2010
DOI: 10.1021/jf904356q
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Dependent Allergic Responses Are Inhibited by Ethanolic Extract of Adlay (Coix lachryma-jobi L. var. ma-yuen Stapf) Testa

Abstract: Allergy is an immune dysfunction caused by degranulation from mast cells in the early phase and cytokine secretion in the late phase of the cell. The purpose of this study was to investigate the effects of adlay (Job's tears, Coix lachryma-jobi L. var. ma-yuen Stapf) testa against beta-hexosaminidase release as a marker of degranulation in rat basophilic leukemia (RBL)-2H3 cells. The ethyl acetate fraction from ethanolic extracts of adlay testa (ATE-EtOAc) exhibited potent inhibitory activity that suppressed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 20 publications
2
42
0
2
Order By: Relevance
“…It is a nourishing food, and is also used in traditional Chinese medicine (Chung et al, 2011). Due to its beneficial efficacies including anti-inflammation, anticancer, and analgesic effects (Chen, Shih, Hsu, & Chiang, 2010;Seo et al, 2000), adlay is usually used for the treatment of warts, chapped skin, rheumatism and neuralgia. It is also used as an anti-inflammatory and antihelmintic agent (Chen, Chung, Chiang, & Lin, 2011;Kuo, Shih, Kuo, & Chiang, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is a nourishing food, and is also used in traditional Chinese medicine (Chung et al, 2011). Due to its beneficial efficacies including anti-inflammation, anticancer, and analgesic effects (Chen, Shih, Hsu, & Chiang, 2010;Seo et al, 2000), adlay is usually used for the treatment of warts, chapped skin, rheumatism and neuralgia. It is also used as an anti-inflammatory and antihelmintic agent (Chen, Chung, Chiang, & Lin, 2011;Kuo, Shih, Kuo, & Chiang, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Adlai is also widely planted in Taiwan, China, and Japan, where it is considered a healthy food supplement. It is also used to treat warts, chapped skin, rheumatism and neuralgia and various parts of the adlai plant have notable anticancer (Lee et al, 2008), anti-inflammatory (Seo et al, 2000) and anti-allergic properties (Chen et al, 2010b). However, the adlai shell, which constitutes half of the grain by weight, is regarded as waste.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, flavonoids were reported to show antimicrobial (Cushnie & Lamb, 2006, anti-allergic (Chen et al, 2010), anti-inflammatory (Seo et al, 2000), and anticarcinogenic (Lee et al, 2008) activities. Until 2004, it was suggested Lamb, 2005, 2011) that their antibacterial efficacy was dependent upon cytoplasmic membrane damage by perforation (Ikigai et al, 1993), inhibition of nucleic acid synthesis (Mori et al, 1987) and disruption of energy metabolism due to NADH-cytochrome c reductase inhibition (Haraguchi et al, 1998).…”
mentioning
confidence: 98%